2017
DOI: 10.3390/ijms18051102
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as Theranostic Vehicles in Experimental and Clinical Applications—Focus on Prostate and Breast Cancer

Abstract: Prostate and breast cancer are the second most and most commonly diagnosed cancer in men and women worldwide, respectively. The American Cancer Society estimates that during 2016 in the USA around 430,000 individuals were diagnosed with one of these two types of cancers, and approximately 15% of them will die from the disease. In Europe, the rate of incidences and deaths are similar to those in the USA. Several different more or less successful diagnostic and therapeutic approaches have been developed and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 569 publications
(681 reference statements)
0
59
0
Order By: Relevance
“…Since cancer is a world health problem, emerging drug preparations that can pass through tumor barriers and enhance anticancer drug delivery are potentially useful [2]. In this context, a lot of research has been done to synthesize new classes of materials, including those at nanoscale, and test their anticancer properties and/or their application in cancer early detection approaches [3,4]. Silver nanoparticles (AgNPs) are widely applied in cancer research due to their potent in vitro antitumor effects on cancer cell lines including breast and cervical cancer models [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Since cancer is a world health problem, emerging drug preparations that can pass through tumor barriers and enhance anticancer drug delivery are potentially useful [2]. In this context, a lot of research has been done to synthesize new classes of materials, including those at nanoscale, and test their anticancer properties and/or their application in cancer early detection approaches [3,4]. Silver nanoparticles (AgNPs) are widely applied in cancer research due to their potent in vitro antitumor effects on cancer cell lines including breast and cervical cancer models [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Fernández Martínez et al [235] published the design of an AI algorithm based on machine learning that was able to help oncologists to detect different TNBC subtypes for optimizing therapeutics. In the near future, a sophisticated AI could feed back different databases such as TCGA (The Cancer Genome Atlas) [236,237] which contains SNP-based platforms, reverse-phase protein array (RPPA), DNA and RNA sequencing among other useful critical information working in conjunction with METABRIC (Molecular Taxonomy of the Breast Cancer International Consortium) [238] to study molecular heterogeneity in various molecular subtypes of breast cancer including TNBC, they could provide valuable Big Data (clinical history, transcriptomic, recurrence, prognosis, treatment, etc.) for oncologist to bring personalized medicine to these patients in a reasonable time.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Previous studies have shown that ultrasound molecular imaging provides new ideas for early diagnosis, treatment and e cient monitoring of prostate cancer due to its real-time dynamic imaging, therapeutic controllability and easy operation [4,5]. However, due to the poor sensitivity and speci city of conventional ultrasound in the diagnosis of prostate cancer, the development of an ultrasound contrast agent with good sensitivity and strong contrast is urgent for current research in prostate cancer ultrasound molecular imaging [6]. Near-infrared uorescence imaging has the advantages of real-time imaging, high sensitivity, no ionizing radiation use and reduced cost.…”
Section: Introductionmentioning
confidence: 99%